PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL, DAN LOAN TO DEPOISIT RATIO TERHADAP PERUBAHAN LABA ( Studi Kasus Bank Konvensional Yang Terdaftar di BEI Periode 2009-2012) - Dita Nur Raifah; Teguh Erawati (Jurnal Akuntansi, 2015)
This study discusses the changes in earnings and financial ratios based on financial statements of listed companies in Indonesia Stock Exchange during the period 2009-2012. The purpose of this study was to determine whether the Capital Adequacy Ratio (CAR) , Non- Performing Loans (NPL) , Operating Expenses Operating Income (BOPO) , and the Loan to Deposit Ratio (LDR) has an influence on incomen changes. The type of data in this study is secondary . Sampling in this study using purposive sampling method . Companies that used a sample of 24 banking companies listed in Indonesia Stock Exchange during 2009-2012. This research is quantitative , and statistical tests use the test multiple linear regression. By using regression analysis , it can be seen that the Capital Adequacy Ratio (CA ) , Non Performing Loans (NPL) , Operating Expenses Operating Income (BOPO) , and the Loan to Deposit Ratio (LDR) has a significant effect on earnings changes . Partial test results , the Capital Adequacy Ratio (CAR) has a positive and significant effect on earnings changes . Non Performing Loan (NPL) had no effect on earnings changes . Operating Expenses Operating Income does not affect the income changes . Loan to Deposit Ratio (LDR) has a positive and significant effect on earnings changes. Keywords : Capital Adequacy Ratio (CAR) , Non-Performing Loans (NPL) , Operating Expenses Operating Income (BOPO) , and the loan to deposit ratio (LDR) , and Income Changes .